The Microstructure and Hardness Properties of ZrO2+Y2O3/Al2O3 Layers Coated by Using Plasma Spray Process on Al Bronze Surface - Ozel, Serkan; Turhan, Huseyin (Carl Hanser Verlag, 2010)
In this study, ZrO2 + Y2O3/Al2O3 powders were coated on the surface of aluminum bronze (Cu + 5 % Al) by using the atmospheric plasma spraying method. The effect of Al2O3 on microstructure and hardness was examined in four different coatings applied by using 5-10-20 % Al2O3 ratio in ZrO2 + Y2O3 and ZrO2 + Y2O3. For this purpose, microstructure images of the coated layers were taken in optical microscope and SEM, EDX and XRD analyses were performed and their microhardness values were measured. It was observed that a porous structure occurred in the coatings containing ZrO2 + Y2O3/Al2O3. The coatings containing Al2O3 showed higher microhardness values than the one without Al2O3, and depending on the increase of Al2O3 amount, the amount of porosity increased and microhardness value decreased.
Keywords: Thermal Barrier Coatings; Aluminum; Particle; Ysz